Features of chicken egg yolk immunoglobulin (IgY) against the infection of red-spotted grouper nervous necrosis virus. Issue 80 (September 2018) - Yi, Lizhu; Qin, Zhendong; Lin, Hanzuo; Zhou, Yang; Li, Jiabo; Xu, Zhen; Babu V, Sarath; Lin, Li
Abstract: Red-spotted grouper nervous necrosis virus (RGNNV) is one of the most important viruses which mainly infects the larva of marine and freshwater fish with high mortality and affects the fishery industry worldwide. Currently, there are no effective vaccines available for the fish larva infected with NNV. Immunoglobulin yolk (IgY) origin of oviparous animals is passed from the blood serum and concentrated in the egg yolk. With the advantages of high yield, cost-effectiveness, and high stability, IgY can be widely used in passive immunization, especially in young animals in which adaptive immunity is not fully developed. In this study, we have cloned and expressed the recombinant capsid protein of RGNNV in Escherichia coli and used as an immunogen for generating specific anti-RGNNV IgY antibody in laying hens. Water-soluble fractions (WSF) of the specific IgY were isolated from egg yolk and purified by two-step precipitation with saturated ammonium sulfate salting. By Enzyme linked immunosorbent assay (ELISA), the titer of the IgY reached a peak at the 6th week post of immunization and had a strong stability at a wide range of temperature, pH, and pepsin enzyme digestion. The purified IgY was competent to neutralize and completely inhibited the RGNNV replication in the grouper fin cell line (GF-1), indicating that it was highly specific and effectively recognized RGNNV. The results will pave a new way for the prevention of RGNNV infection. Highlights: High titer of specific IgY against RGNNV was obtained from rCP immunized hen eggs. Anti-RGNNV IgY possessed high stability at wide ranges of temperature, pH and pepsin. Anti-RGNNV IgY had a strong affinity to rCP and RGNNV. Anti-RGNNV IgY had the potential to neutralize the RGNNV replication in a dose-dependent manner.